KONFLIK SOSIAL MASYARAKAT KAMPUNG BOTUNG KENAGARIAN KOTA NOPAN KECAMATAN RAO UTARA KABUPATEN PASAMAN (Studi Kasus Pemanfaatan Lahan) - Esharyadi "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The research was conducted with purpose to know the factors, the effects,and the solutions of the field’s use conflict in Kampung Botung. This researchused qualitative descriptive method that have five respondents to representative ofkampung Botung society. To collected the data, researcher used observation,interview and dokumentation. From the research finding, it can be included thathuman is the creature that have many need in their life and it can be a reason whythe social conflict happen in the society. Based on the research, the social conflictof the field’s use happened in Kampung Botung society. Until now, this problemhave finished not because there were many individual importances. To solved thisproblem, the society used negotation and mediator, but it did not can solveeffectively. But, the two Kampung’s leader did not agreed so that the kampungBotung is seperated by two parts, kampung Botung Atas and Kampung BotungBawah.Key words : social conflict, field’s use.